1996
DOI: 10.1029/96jd02159
|View full text |Cite
|
Sign up to set email alerts
|

Models of lightning‐produced sprites and elves

Abstract: Three different types of optical phenomena have been observed at high altitude above thunderstorms: an enhanced airglow ("elves") at roughly ---90 km; a reddish glow ("sprites") from 50 to 90 km; and an upward moving, bluish emission ("jets") below 40 km. A likely explanation for some or all of these phenomena is gas breakdown caused by the electromagnetic fields of lightning discharges. This paper examines the connection between these fields and breakdown at high altitude, using both analytic models and numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 20 publications
(18 reference statements)
4
35
0
1
Order By: Relevance
“…The observed initiation height, •>300 C.km parent discharge charge moment changes [Cureruer and Huang et al, 1999], and corona streamer characteristics [Stanley et al, 1999a] are consistent with a conventional breakdown mechanism for sprite initiation and development under the influence of a CG's quasi-electrostatic field [Wilson, 1925;Fernsler and Rowland, 1996;Pasko et al, 1998]. During the daytime, ionospheric conductivity is greatly enhanced at the altitudes of nighttime sprite initiation.…”
mentioning
confidence: 68%
“…The observed initiation height, •>300 C.km parent discharge charge moment changes [Cureruer and Huang et al, 1999], and corona streamer characteristics [Stanley et al, 1999a] are consistent with a conventional breakdown mechanism for sprite initiation and development under the influence of a CG's quasi-electrostatic field [Wilson, 1925;Fernsler and Rowland, 1996;Pasko et al, 1998]. During the daytime, ionospheric conductivity is greatly enhanced at the altitudes of nighttime sprite initiation.…”
mentioning
confidence: 68%
“…Haldoupis et al (2009), from a modeling study on the relaxation of early VLF events associated with TLEs, have shown that events with shorter recoveries are likely to come from lower altitudes compared with events with longer recoveries. Also it has been estimated that an unusually large charge moment change of about 8000 C-km is required to initiate a daytime sprite at a 50-km altitude (Fernsler and Rowland, 1996). Stanley et al (2000) detected 3 separate daytime sprites on 14 August, 1998, via a unique sprite ELF signature recorded at a site in New Mexico, following exceptionally large lightning discharges.…”
Section: Resultsmentioning
confidence: 99%
“…These electric fields may accelerate thermal electrons to energies of a few eV which are required to generate light and ionization (conventional breakdown) [Fernsler and Rowland, 1996; 1997], and they may also accelerate MeV electrons produced by cosmic rays into an upward propagating, avalanching beam of runaway electrons (runaway breakdown) [Lehtinen et al, 1997;Yukhirnuk et al, 1998]. A critical parameter in each of these theories is the electric charge moment change created by the parent lightning discharge, which is directly related to the quasi-static mesospheric electric field thought to be the driving force in sprite generation.…”
Section: Introductionmentioning
confidence: 99%